FROM WARRIORS TO UNITY: ANALYSING FANTASY FORMULA IN RAYA AND THE LAST DRAGON (2011) - Tasari, Putri Devi; Assiddiqi, Hasbi (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
This research aims to analyze the conflict formula in Raya and The Last Dragon, directed by Carlos LÃ³pez Estrada and Don Hall. The film portrays the story of Raya, a female warrior in a country abundant with animals and a unique mode of transportation called Tuktuk, before it turns dystopian. The scenes from the film represent the cultural diversity of Southeast Asia. The research method employs a descriptive quantitative approach, analysing data and sources through the intrinsic elements of the film. Data collection techniques include documentation techniques, such as films and literary observations, and interactive techniques, such as data reduction, data presentation, and data collection. The writer applies literary theory to comprehend the literary systematics in films. The findings of this study reveal that Raya and The Last Dragon presents Kumandra as a country that exemplifies Southeast Asian civilization, aiming to demonstrate tolerance, resilience, acceptance, and unity.